Gallium arsenide 0.5–18 GHz antenna front‐end with integrated limiter and differential to single ended low‐noise amplifier. Issue 6 (5th April 2018) - Pantoli, Leonardo; Stornelli, Vincenzo; Leuzzi, Giorgio; Bartocci, Marco; Trotta, Fabrizio; Gaetano, Domenico; Manna, Antonio; Ciacia, Egidio; Di Paolo, Franco
Abstract : In this study, the authors present a 36:1 relative bandwidth active front‐end low‐noise amplifier (LNA) with power limiter that has been developed for airborne ultra‐wideband receiver systems. The proposed system is driven by an external antenna with a balanced mode with an input impedance of 150 Ω. The whole microwave monolithic integrated circuit (MMIC) embeds a protection from the presence of high‐level signals, an ultra‐wideband amplifier circuit, an active balun and an impedance transformer. It has a bandwidth ranging from 0.5 to 18.0 GHz with 14 dB gain, 4.5 dB noise figure (NF), 20 dB common‐mode rejection and 30 dBm input overload protection. The circuit has a single bias from the output port greatly simplifying its use within a receiving system and can be directly integrated into the antenna mechanical support. Test measurements are also provided.